Cost‐effective regulation of nonpoint emissions from pastoral agriculture: a stochastic analysis. (10th December 2013) - Doole, Graeme J.; Romera, Alvaro J.
<x xml:space="preserve">Abstract</x> Nutrient emissions from pastoral agriculture are a global cause of declining water quality. Their management is complicated through variability arising from climate and soil influences. This paper compares the implications of input‐based policies and direct restrictions on leaching to achieve 10 and 20 per cent reductions in nitrogen (N) load, in the context of pasture‐based New Zealand dairy farms. The most important mitigation practices on these farms are de‐intensification (involving reductions in N fertiliser application and stocking rate) and the application of nitrification inhibitors. A stylised conceptual model, incorporating both sources of variability, is used to identify the implications of alternative policies. Direct restriction of estimated N leaching is the most cost‐effective policy to reduce N leaching by 10 and 20 per cent. These results indicate the general insufficiency of input‐based mechanisms for water quality improvement, given the low correlation between input use and leaching, possible substitution with unrestricted inputs and their failure to motivate the use of mitigation strategies. Additionally, model output indicates that inherent variability in water quality, mainly due to climate influences, can dominate the benefits of regulatory action in any given year.